Perinatal Exogenous Nitric Oxide in Fawn-Hooded Hypertensive Rats Reduces Renal Ribosomal Biogenesis in Early Life - Wesseling, Sebastiaan; Essers, Paul B.; Koeners, Maarten P.; Pereboom, Tamara C.; Braam, Branko; van Faassen, Ernst E.; MacInnes, Alyson W.; Joles, Jaap A. (Frontiers in Genetics, 2011)
Nitric oxide (NO) is known to depress ribosome biogenesis in vitro. In this study we analyzed the influence of exogenous NO on ribosome biogenesis in vivo using a proven antihypertensive model of perinatal NO administration in genetically hypertensive rats. Fawn-hooded hypertensive rat (FHH) dams were supplied with the NO donor molsidomine in drinking water from two weeks before to four weeks after birth, and the kidneys were subsequently collected from 2 day, 2 week and 9-10 month old adult offspring. Although the NO donor increased maternal NO metabolite excretion, the NO status of juvenile renal (and liver) tissue was unchanged as assayed by EPR spectroscopy of NO trapped with iron-dithiocarbamate complexes. Nevertheless, microarray analysis revealed marked differential up-regulation of renal ribosomal protein genes at 2 days and down-regulation at 2 weeks and in adult males. Such differential regulation of renal ribosomal protein genes was not observed in females. These changes were confirmed in males at 2 weeks by expression analysis of renal ribosomal protein L36a and by polysome profiling, which also revealed a down-regulation of ribosomes in females at that age. However, renal polysome profiles returned to normal in adults after early exposure to molsidomine. No direct effects of molsidomine were observed on cellular proliferation in kidneys at any age, and the changes induced by molsidomine in renal polysome profiles at 2 weeks were absent in the livers of the same rats. Our results suggest that the previously found prolonged antihypertensive effects of perinatal NO administration may be due to epigenetically programmed alterations in renal ribosome biogenesis during a critical fetal period of renal development, and provide a salient example of a drug-induced reduction of ribosome biogenesis that is accompanied by a beneficial long-term health effect in both males and females.